PENGENDALIAN WAKTU DAN PENJADWALAN ULANG MENGGUNAKAN METODE CPM (CRITICAL PATH METHOD) - Purwantoro, Almuntofa; To’unni, Attie Wawey Lagi; Uda, Subrata Aditama K.A. (Jurnal Civil Engineering Study, 2024)
In some development projects, finishing the work inside a restricted time is normal. This can never again be kept away from after the utilization of labor with is presently not equally. CPM (Critical Path Method) is a critical path the that intends to decide project arranging and time estimates that are deterministic/positive. Poin of investigation utilizing this method is to decide the time and cost of the undertaking and figure out what activities are remembered for the fundamental activities. Project arranging helps show the relationship of every development to various activities and normal assignments, recognizes which connections ought to come first among activities, and shows pragmatic time measures for each activity. Time control made no difference and the rescheduling results acquired for Development project the CPM (Critical Path Method) strategy were gotten in 300 days as per the underlying term of work.